Pengaruh Kontribusi Pajak Bumi Dan Bangunan (PBB) Dan Pajak Hotel Terhadap Peningkatan Pendapatan Asli Daerah - Revana Sheviani Sugianto; Anissa Yuniar Larasati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study has the objective of analyzing the effect of the Contribution of Land and Building Tax (PBB) and Hotel Tax on Increasing Regional Original Income in Cimahi City in 2017-2021. This type of research is quantitative and uses a descriptive-associative approach. Collecting research data using library research and documentation methods. Monthly data on receipt of the Regional Revenue Realization Report in Cimahi City for 2017-2021 were selected as the study population. Saturated sampling technique was used for sampling. The results of this study partially show that the increase in PAD is not affected by the PBB contribution, while the increase in PAD is negatively and significantly affected by the hotel tax contribution. While simultaneously/together with the Contribution of Land and Building Tax (PBB) and Hotel Tax have a significant effect on the Increase of Regional Original Income. Keywords: Contribution, Land and building tax, Hotel Tax, Locally Renerated Revenue